Comparative Study of the Effects of Tai Chi and Square Dance on Immune Function, Physical Health, and Life Satisfaction in Urban Empty-Nest Older Adults - Su, ZhongJun; Zhao, JieXiu (Frontiers in Physiology, 2021)
Objective: To compare the effects of Tai Chi and Square dance on immune function, physical health, and life satisfaction in urban, empty-nest older adults. Methods: This cross-sectional study included 249 older adults (60-69 years) who were categorized into Tai Chi (n=81), Square dance (n=90), and control groups (n=78). We evaluated immunoglobulin G (IgG) and interleukin-2 (IL-2) levels by enzyme-linked immunosorbent assay (ELISA), natural killer (NK) cell cytotoxicity by MTT assay, physical health indices by physical fitness levels, and life satisfaction by Life Satisfaction Index A (LSIA) scores. Results: Immune function, physical health, and life satisfaction in older adults in the Tai Chi and Square dance groups were significantly better than those in the control group (P<0.05). Regarding immune function and physical health, the Tai Chi group exhibited significantly higher levels of IgG (15.41±0.26 g/L vs. 11.99±0.35 g/L, P<0.05), IL-2 (4.60±0.20 ng/mL vs. 4.45±0.21 ng/mL, P<0.05), and NK cell cytotoxicity (0.28±0.02 vs. 0.22±0.02, P<0.05) than the square dance group, significantly lower waist-to-hip ratio (0.87±0.02 vs. 0.89±0.02, P<0.05), resting pulse (78.4±4.6 beats/min vs. 81.0±3.1 beats/min, P<0.05), systolic blood pressure (132.0±5.2 mmHg vs. 136.2±3.2 mmHg, P<0.05), diastolic blood pressure (80.0±2.6 mmHg vs. 83.0±2.7 mmHg, P<0.05), and significantly higher vital capacity (2978.0±263.0 mL vs. 2628.3±262.8 mL, P<0.05) and duration of one-leg standing with eyes closed (16.2±1.9 s vs. 12.0±1.7 s). However, there was no significant difference in LSIA scores between the Tai Chi and Square dance groups (12.05±1.96 vs. 13.07±1.51, P>0.05). Further, there was a significant correlation between LSIA scores and immune function (r=0.50, P=0.00) and physical health (r=0.64, P=0.00). Conclusions: (1) Both Tai Chi and square dance practitioners had better health outcomes, compared with sedentary individuals; (2) Tai Chi practitioners had better physical health and immune function than Square dance practitioners. (3) Tai Chi and Square dance exercises had similar effects on life satisfaction among urban empty-nest older adults. Suggestions: For urban empty-nest older adults who want to have better physical health and immune function, long-term Tai Chi exercise may be a better choice; however, those who are concerned about life satisfaction can choose either Tai Chi or Square dance exercise.